Canonical Correlation Analysis of bidirectional Linkages Between Agricultural Productivity and Household Welfare Development in Nepal (Janapriya Journal of Interdisciplinary Studies, 2025)
This study explores how agriculture and household welfare are connected in Nepal using census data from 2001, 2011, and 2021. Two sets of indicators were created to represent structural changes in agriculture and household living conditions. All variables were standardized, and data checks using KMO, Bartlett’s test, and Cronbach’s alpha confirmed that the indicators were suitable for multivariate analysis (KMO: 0.76–0.84; Bartlett’s p-value